Magic in Private and Public Lives of the Ancient Romans - Kaczor, Idaliana (Collectanea Philologica, 2020)
The Romans practiced magic in their private and public life. Besides magical practices against the property and lives of people, the Romans also used generally known and used protective and healing magic. Sometimes magical practices were used in official religious ceremonies for the safety of the civil and sacral community of the Romans.